Getting food during the German occupation of Western Finnmark (1940–1944) - Bogomolov, Yaroslav (Septentrio Conference Series, 2015)
In this article the author describes the food supply in the western part of Finnmark County. Despite the fact that the authorities tried to control the food supplies and secure equal access to food for all inhabitants, food distribution was never equal and civilians had to work hard and use their imagination in order to get some food to eat.